1989
DOI: 10.1161/01.hyp.14.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular vascular muscle Ca2+ modulation in genetic hypertension.

Abstract: Distribution of intracellular free calcium concentration (Ca2+) was compared in spontaneously hypertensive rat (SHR) and Wistar-Kyoto (WKY) rat isolated vascular muscle cells at rest and during stimulation by K+ with Ca2+ agonist or antagonist. Ca2+ activity was quantitated at each point within vascular muscle cells loaded with fura-2 at fluorescence excitation wavelengths of 340, 360, and 380 nm, and fluorescence emission at 510 nm (all filters were +/- 5 nm) quantitated by a digital photon-counting camera. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…Ion channel changes such as these are thought to underlie increased vascular reactivity in hypertension (11,20). It is generally agreed that depolarization (17,18), enhanced Ca 2ϩ current (15,32,35), and increased intracellular free Ca 2ϩ (13,21,31) contribute to augmented vasoconstriction in hypertension. Importantly, however, roles for smooth muscle K ϩ channels in producing or opposing hypertension are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Ion channel changes such as these are thought to underlie increased vascular reactivity in hypertension (11,20). It is generally agreed that depolarization (17,18), enhanced Ca 2ϩ current (15,32,35), and increased intracellular free Ca 2ϩ (13,21,31) contribute to augmented vasoconstriction in hypertension. Importantly, however, roles for smooth muscle K ϩ channels in producing or opposing hypertension are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it was reported that impaired insulin sensitivity or associated hyperinsulinemia can depress the activity of the Na-K pump [16], augment Na-H exchange [17], and impair Ca-ATPase [18], suggesting that resistance to insulin-stimulated glucose uptake and hyperinsulinemia are involved in the etiology and clinical course of hypertension [2,19]. Blood pressure in the present subjects was decreased to normal by VLCD therapy, but there was no difference between blood pressure before and after mazindol therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased PLC activity and increased intracellular calcium are already observed in prehypertensive spontaneously hypertensive rats (24,26 (27) reported that the shear stress-induced increase in 'P3 in human umbilical vein endothelial cells persists for several minutes after an increase in shear stress, although other agonist-induced IP3 levels, such as those induced by histamine, thrombin, and bradykinin, return to near basal levels within 1 to 2 min after exposure to the agonist. Pressure-induced calcium responses were sustained and also differed from those of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%